Managing change : enquiry and action - Beech, Nic; MacIntosh, Robert (Cambridge : Cambridge University Press, 2012)
The ability to manage change successfully is an essential part of business. It is a skill that is much valued by employers, and it is therefore one of the most commonly delivered courses. This book helps you to understand three key activities for managing change: diagnosing, explaining and enacting. Both practical and action-oriented, it gives students and managers the tools they need to deal with the messy reality of change. It combines theory and diagnostic tools with practical examples that focus on actions and outcomes. It also includes short vignettes and longer cases, from a range of international contexts, for classroom study or for use on distance learning courses. Managing Change is written for advanced undergraduates and graduate students taking modules on change management, strategy and organizations. Its class-tested approach has been successfully delivered in a wide variety of settings, including over fifty executive short courses with FTSE-listed businesses.
List of figures -- List of tables -- List of cases -- Acknowledgements -- 1. Pratising change management -- 2. Current perspectives and classic ideas -- 3. Clarity and ambiguity -- 4. Engagement and vitality -- 5. Stakeholder positioning and dynamics -- 6. Culture, habits and unlearning -- 7. Changing structure -- 8. Identity and chnage -- 9. Choosing customers and competitors -- 10. Changing processes -- 11. Aligning people and activities -- 12. Learning and developing -- 13. Changing through dialogue -- 14. Developing/interpreting evidence, reflexive learning -- 15. Accounting for change -- 16. The enquiry-action framework in practice -- Case 1. ABB -- Case 2. ITS canada -- Case 3. Island opera -- Case 4. Oticon -- Case 5. Admiral insurance -- Case 6. Power provision plc -- Case 7. Nokia -- Case 8. Her majesty's revenue and customs -- Case 9. Apple -- Index.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Organizational change; Organizational change -- Management